Linguo-didactic aspect of formation of the professionally-oriented lexical competence of students of the specialty “Jurisprudence” - Kosovych Оlga; Sokol, Maryana (ScienceRise: Pedagogical Education, 2020)
The article notes that the generated lexical competence involves the mastery of the students with the values of a lexical unit, its spelling and pronunciation, knowledge of the grammatical forms of a word, synonyms and antonyms and by mastering the rules of compatibility with other lexical units. Exercises are an integral part of the formation and improvement of the professionally-oriented lexical competence. They are used at the stages of forming and developing lexical skills. The foreign language professionally oriented vocabulary teaching is based on general didactic principles (availability; scientific content; consciousness; activity; systematic character; consistency and durability of mastering of knowledge, abilities and skills; use of visual methods) and methodological principles (stimulating and motivating a positive attitude to learning a foreign language for specific purposes; considering the individual characteristics of students; professional orientation of teaching foreign language vocabulary; taking into account the degree of professional training of students and the conformity of the content of foreign lexical material to needs of their future professional activities); the principle of systemic learning of a professionally-oriented lexical material on the basis of complex non-communicative and conditionally communicative exercises with an interrelated improvement of skills and abilities of reading, speaking and writing professional orientation, as the formation of the professionally oriented lexical competence should be arranged through the set of exercises, in which the basic principles and training content are implemented. The formation of the professionally-oriented lexical competence has an impact on the improvement and development of the professionally oriented foreign language communicative competence as a whole. The ability to read and understand professionally-oriented literature and carry out professional communication depends on the level of lexical competence formation. In general, in the context of contemporary education the attention should be focused primarily on the new standards, the idea of which should be based on the competence approach, which includes the formation of general competences and needs of the labor market. To stop the outflow of future or practicing lawyers is possible only due to the quality of higher education, which is constantly growing, and is aimed at the expectations of the labour market, as well as it is pursuing a preemptive tactic. Today it is necessary to conduct the mandatory formation of general competences, readiness for the challenges that may appear in the near future